Ca2+ Signaling in Cardiovascular Fibroblasts - Andreas Rinne; Florentina Pluteanu (Biomolecules)
Fibrogenesis is a physiological process required for wound healing and tissue repair. It is induced by activation of quiescent fibroblasts, which first proliferate and then change their phenotype into migratory, contractile myofibroblasts. Myofibroblasts secrete extracellular matrix proteins, such as collagen, to form a scar. Once the healing process is terminated, most myofibroblasts undergo apoptosis. However, in some tissues, such as the heart, myofibroblasts remain active and sensitive to neurohumoral factors and inflammatory mediators, which lead eventually to excessive organ fibrosis. Many cellular processes involved in fibroblast activation, including cell proliferation, protein secretion and cell contraction, are highly regulated by intracellular Ca2+ signals. This review summarizes current research on Ca2+ signaling pathways underlying fibroblast activation. We present receptor- and ion channel-mediated Ca2+ signaling pathways, discuss how localized Ca2+ signals of the cell nucleus may be involved in fibroblast activation and present Ca2+-sensitive transcription pathways relevant for fibroblast biology. When investigated, we highlight how the function of Ca2+-handling proteins changes during cardiac and pulmonary fibrosis. Many aspects of Ca2+ signaling remain unexplored in different types of cardiovascular fibroblasts in relation to pathologies, and a better understanding of Ca2+ signaling in fibroblasts will help to design targeted therapies against fibrosis.